On the combined maintenance and routing optimization problem. (January 2016) - López-Santana, Eduyn; Akhavan-Tabatabaei, Raha; Dieulle, Laurence; Labadie, Nacima; Medaglia, Andrés L.
Abstract: This work focuses on the problem of planning and scheduling maintenance operations for a set of geographically distributed machines, subject to non-deterministic failures with a set of technicians that perform preventive maintenance and repair operations on the machines at the customer sites within a specific time window. This study presents a two-step iterative approach. In the first step, a maintenance model determines the optimal time until the next preventive maintenance operation, its frequency, and the time window for each customer, while minimizing the total expected maintenance costs. In the second step, a routing model assigns and schedules maintenance operations to each technician over the planning horizon within the workday. This two-step iterative process balances the maintenance cost, the failure probabilities, and waiting times at each customer. The novelty of this work lies in the integration of maintenance scheduling and a routing model that considers several machines. Highlights: The paper focuses on planning and scheduling maintenance operations. We present a joint maintenance and routing model for scattered machines. We propose a two-step iterative approach to find a solution. We illustrate the performance of this model on a case in oil and gas.